General Aspects Concerning the Principles of Insolvency Proceedings - Bularca Anca Roxana (Bulletin of the Transilvania University of Braşov, 2015)
Insolvency proceedings represent a special judicial procedure regulated by Law no.85/2014 on insolvency prevention and insolvency proceedings, also known as the Insolvency Code. This law has regulated distinctly the fundamental principles underlying its application. These principles are based on the recommendations of the World Bank and the International Monetary Fund, which have contributed substantially to the adoption of the project of this law. Due to the fact that Law no.85/2014 has stated expressly the principles underlying its enforcement, has included the concepts of insolvency of a group of companies and insolvency of entities with extraneous elements, the Insolvency Code is deemed as one of the most advanced legislations at EU level.